THE EFFECTIVENESS OF APPLICATION OF LAICITE IN SECULARISM LIFE IN FRANCE TO MINIMIZE RELIGIOUS RADICALIZATION GROUPS: THE EFFECTIVENESS OF APPLICATION OF LAICITE IN SECULARISM LIFE IN FRANCE TO MINIMIZE RELIGIOUS RADICALIZATION GROUPS - Rezky Apriliantini; Visa Juliansyah; Rachma Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2021)
This paper aims to explain how the effectiveness of the application of Laicite in the life of secularism in France in minimizing religious radicalization groups in that country. The author team uses Constructivism theory and uses the concept of Human Security. The author's team used a descriptive research method with a qualitative approach. Data collection techniques used are literature study in the form of books, literature, previous research journals, and from news websites. The results of the research in this paper indicate that there is an effective role in the application of Laicite in the life of secularism in France in minimizing religious radical groups in the country. Through constitutional authority in the form of the Laicite Law, it can strengthen the existence of laws which must be understood that France separates religious affairs and state government affairs. Keywords: Laicite, Separatism, Secularism, France.